Consumer’s Willingness to Pay for Premium Food in Kathmandu Valley - Agrawal, Harshit; Joshi, Neelow Babu; Shrestha, Erisha; Singal, Nishi; Aryal, Ashutosh; Pradhan, Subhra (New Perspective: Journal of Business and Economics, 2023)
The COVID-19 pandemic has led to an increase in consumers' willingness to pay for premium priced foods. This study aims to identify the major factors affecting consumers' willingness to pay for premium priced food. Primary data was collected for this study, and the data was accepted based on the Cronbach alpha test. The study found that consumers' willingness to pay for premium priced food is not affected by hygiene. However, premium price, taste, ambiance, and quality service are factors that affect consumers' willingness to pay. The findings of this study are consistent with previous research that highlights the importance of taste and quality service in influencing consumers' purchase intention. The study also emphasizes the significance of ambiance and premium price in driving consumers' willingness to pay for premium priced food. The study suggests that companies should focus on providing quality service and creating a pleasant ambiance to enhance consumers' willingness to pay for premium priced food. Additionally, companies should consider the premium price of their products and align it with the perceived value of their target market. Overall, the study provides insights into the factors that influence consumers' willingness to pay for premium priced food. The findings of this study can be useful for companies in designing their marketing strategies and enhancing the effectiveness of their product offerings.